Effects of fetal calf serum on cGMP pathway and oocyte lipid metabolism in vitro - Schwarz, Katia R. L. (2017)
Intracellular levels of cyclic nucleotides, such as cGMP, are involved in the regulation of adipocyte lipolysis. Cumulus-oocyte complexes (COCs) express enzymes that both synthesise (guanylate cyclase) and degrade (phosphodiesterase (PDE) 5A) cGMP. Because serum interferes with lipid metabolism, its effects on the cGMP pathway and lipid content in bovine COCs were examined. COCs were matured in medium containing fetal calf serum (FCS; 2% or 10%) or 0.4% bovine serum albumin (BSA; control). At both 2% and 10%, FCS decreased cGMP levels in COCs compared with BSA (0.64 and 1.04 vs 9.46 fmol per COC respectively; P < 0.05) and decreased transcript levels of guanylate cyclase 1, soluble, beta 3 (GUCY1B3), whereas PDE5A levels were increased. FCS also affected the expression of genes related to lipolysis, increasing relative expression of perilipin 2 (PLIN2) and carnitine palmitoyltransferase 1B (CPT1B) in cumulus cells. Effects of FCS and cGMP on the lipid content of oocytes and embryos were evaluated by Nile red staining. COCs were matured with 10% FCS, FCS + 10(-5) M sildenafil (SDF), a PDE5 inhibitor, or 0.4% BSA. The lipid content was increased in oocytes matured in FCS compared with BSA (fluorescence intensity 20.1 vs 17.61 respectively; P < 0.05), whereas the lipid content in oocytes matured in FCS+SDF (fluorescence intensity 16.33) was similar to that in the BSA-treated group (P > 0.05). In addition, lipid content was higher in embryos from oocytes matured with FCS than BSA (fluorescence intensity 31.12 vs 22.31 respectively; P < 0.05), but was increased even further in the FCS+SDF-treated group (fluorescence intensity 40.35; P < 0.05), possibly due to a compensatory mechanism during embryo culture without SDF for the reduction in lipid content during IVM. The present study provides, for the first time, evidence that the cGMP pathway may be involved in lipid metabolism in bovine COCs and that this pathway is affected by FCS.